Social Determinants of Health in The Maritim Sector: A Qualitative Analysis of The Role of Safety Culture And Leadership on The Health and Performance of Stevedores at Tanjung Perak Port - Saktyawan Dwiki Pamungkas; Ramadhan Hasri Harahap; Mauritz Hm Sibarani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This qualitative study investigates the critical influence of workplace culture and leadership styles on occupational health and safety (OHS) outcomes for stevedores at Tanjung Perak Port, Indonesia. Framed within the public health concept of social determinants of health, the research employed a phenomenological approach, conducting in-depth interviews with ten stevedores to capture their lived experiences. Thematic analysis revealed a pervasive normalization of risk, where a culture of machismo and fear of reprisal led to the under-reporting of hazards and the acceptance of unsafe practices as an inevitable part of the job. A stark dichotomy in leadership emerged as a pivotal factor, distinguishing between transactional